2021
DOI: 10.1007/s00068-021-01733-w
|View full text |Cite
|
Sign up to set email alerts
|

Proximal humerus fractures (PHFs): comparison of functional outcome 1 year after minimally invasive plate osteosynthesis (MIPO) versus open reduction internal fixation (ORIF)

Abstract: Purpose Osteosynthetic treatment strategies of PHFs include MIPO or ORIF techniques. The aim of this study was to compare the 1 year outcome following either technique in type B PHFs. Methods This study was designed as a retrospective cohort study of patients treated at one academic Level 1 trauma center. Patients from 2009 to 2019 who required surgical treatment of a type B PHF were eligible to be included in this study. Patients with A- or C-type fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…All the studies included in this systematic review reported the complications that occurred in the DP and DS groups ( 5 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ). Overall, there were no differences in the number of complications: 121 in the DP group (28.4%) and 105 in the DS group (29.9%) ( P = n.s.).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the studies included in this systematic review reported the complications that occurred in the DP and DS groups ( 5 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ). Overall, there were no differences in the number of complications: 121 in the DP group (28.4%) and 105 in the DS group (29.9%) ( P = n.s.).…”
Section: Resultsmentioning
confidence: 99%
“…A significantly higher incidence of screw cut-outs/implant loosening was documented in the MIPO group ( n = 36, 10.3%) compared to the ORIF group ( n = 25, 5.6%) ( P = 0.01). However, only five studies ( 27 , 30 , 32 , 34 , 37 ) took into account the complication rate for Neer PHFs type subgroups. Complications for Neer II fractures were described by two studies: out of 71 patients, the complication rate was 8.6% (3 out of 35 patients) in the DP group and 2.8% (1 out of 36 patients) in the DS group ( 30 , 34 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach can minimize surgical trauma, alleviate postoperative pain, expedite the recovery process, and provide better cosmetic outcomes. 12 , 21 , 22 Indeed, research has shown that closed reduction is the greatest challenge in the MIPO technique. In addition, radiation exposure during the procedure is another factor that young orthopaedic physicians consider when opting for open reduction and internal fixation (ORIF) instead.…”
Section: Discussionmentioning
confidence: 99%
“…We defined nonunion as the existence of a fracture line on the radiographic image obtained at the last follow-up as described in a previous report. 8 …”
Section: Methodsmentioning
confidence: 99%